A supramolecular conductive polymer and its preparation method and application, lithium-sulfur battery positive electrode and lithium-sulfur battery
By using supramolecular conductive polymers rich in carboxyl and amide groups as binders in lithium sulfur batteries, the challenges of lithium sulfur batteries in terms of rate performance and long cycle life are solved, and better electrochemical performance and stability are achieved.
Patent Information
- Application Number
- CN202411942178.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-26
- Publication Date
- 2025-04-04
AI Technical Summary
Lithium sulfur batteries have challenges in terms of rate performance and long cycle life. Mainly due to the insulation, volume expansion and poor shuttle effects of sulfur, the commonly used binder PVDF cannot effectively inhibit the shuttle of polysulfides.
A supramolecular conductive polymer is used as the binder for the positive electrode of the lithium sulfur battery. The polymer has rich carboxyl and amide groups, which can effectively anchor and limit lithium polysulfide on the positive electrode side, thereby inhibiting the shuttle effect and reducing volume expansion through a special mesh structure.
It significantly improves the circulation and rate performance of lithium-sulfur batteries, stabilizes the battery capacity, and improves the electrochemical performance.
Smart Images

Figure CN119751896A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of battery materials, and specifically relates to a supramolecular conductive polymer and a preparation method and application thereof, a lithium-sulfur battery positive electrode and a lithium-sulfur battery. Background Art
[0002] Lithium-sulfur batteries have a high theoretical energy density (2600Wh / kg), and elemental sulfur has the advantages of abundant natural resources, wide sources, low cost and environmental friendliness, making it a strong candidate for the next generation of energy storage materials.
[0003] Functionalized binders are an indispensable component in the positive electrode materials of lithium-sulfur batteries. They are responsible for firmly adhering elemental sulfur and conductive agents to the current collector to maintain the integrity and stability of the electrode structure. So far, polyvinylidene fluoride (PVDF), a linear polymer with good electrochemical stability and acceptable physical adhesion, is the most commonly used binder material in lithium-sulfur batteries.
[0004] However, due to the insulating properties of sulfur (including S, Li2S2 and Li2S), large volume expansion (~80%) and poor "shuttle effect", lithium-sulfur batteries have always faced challenges in terms of rate performance and long cycle life. Currently, the commonly used binder PVDF cannot inhibit polysulfide shuttle, and the cycle and rate performance of lithium-sulfur batteries are poor. Summary of the invention
[0005] In view of this, the object of the present invention is to provide a supramolecular conductive polymer and its preparation method and application, a lithium-sulfur battery positive electrode and a lithium-sulfur battery. The supramolecular conductive polymer provided by the present invention is used as a lithium-sulfur battery positive electrode binder, which can effectively improve the cycle and rate performance of the lithium-sulfur battery and is conducive to improving the electrochemical performance of the lithium-sulfur battery.
[0006] The present invention provides a supramolecular conductive polymer having a structure shown in Formula I:
[0007]
[0008] In formula I, n: 24-32, m: 500-1000, x: 2084-2778;
[0009] R is an alkylene group, a substituted alkylene group, an aryl group, or a substituted aryl group.
[0010] The present invention also provides a method for preparing the supramolecular conductive polymer described in the above technical solution, comprising the following steps:
[0011] Mixing polyethylene glycol, isocyanate, malonic acid dihydrazide and an organic solvent to carry out a first polycondensation reaction to obtain a polyurethane solution;
[0012] The polyurethane solution and polyacrylic acid are mixed to carry out a second polycondensation reaction to obtain a supramolecular conductive polymer;
[0013] The structural formula of the isocyanate is shown in Formula II, and the structural formula of the polyacrylic acid is shown in Formula III.
[0014]
[0015] In formula III, y: 6250-8333.
[0016] Preferably, the mass ratio of the polyethylene glycol, isocyanate and malonic acid dihydrazide is 5:(3-4.5):(2-0.5).
[0017] Preferably, the temperature of the first polycondensation reaction is 40 to 80° C., and the time is 10 to 24 hours.
[0018] Preferably, the mass ratio of polyurethane to polyacrylic acid in the polyurethane solution is 1:(1-2).
[0019] Preferably, the temperature of the second polycondensation reaction is 30-60° C., and the time is 24-48 hours.
[0020] The present invention also provides the use of the supramolecular conductive polymer described in the above technical solution or the supramolecular conductive polymer obtained by the above preparation method in a positive electrode binder for a lithium-sulfur battery.
[0021] The present invention also provides a lithium-sulfur battery positive electrode, comprising a current-carrying layer, wherein the sulfur-carrying layer comprises sulfur, a conductive agent and a binder, wherein the binder is the supramolecular conductive polymer described in the above technical solution or the supramolecular conductive polymer obtained by the above preparation method.
[0022] Preferably, the content of the supramolecular conductive polymer in the sulfur-carrying layer is 1 to 20 wt %.
[0023] The present invention also provides a lithium-sulfur battery, comprising an electrolyte, a separator, a negative electrode and a positive electrode, wherein the positive electrode is the positive electrode of the lithium-sulfur battery described in the above technical solution.
[0024] Compared with the prior art, the present invention has the following beneficial effects:
[0025] The present invention provides a supramolecular conductive polymer having a structure shown in Formula I:
[0026]
[0027] In formula I, n is 24 to 32, m is 500 to 1000, and x is 2084 to 2778; R is an alkylene group, a substituted alkylene group, an aryl group, or a substituted aryl group.
[0028] The abundant carboxyl and amide groups in the supramolecular conductive polymer provided by the present invention make the supramolecular conductive polymer have abundant chemical adsorption sites, which can effectively anchor and restrict soluble lithium polysulfide on the positive electrode side, so as to achieve the purpose of inhibiting the shuttle effect, stabilizing the battery capacity, and improving the cycle performance. In addition, the supramolecular conductive polymer provided by the present invention has a special mesh structure, similar to a spider web, which can significantly inhibit the volume expansion during the cycle, is conducive to improving the adhesion of the binder, has good conductivity, improves the cycle performance of the lithium-sulfur battery, and is very beneficial to the improvement of the electrochemical performance. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0030] Figure 1 FT-IR spectrum of the supramolecular conductive polymer TASP prepared in Example 1;
[0031] Figure 2 This is the EIS spectrum of the sulfur positive electrode of the lithium-sulfur battery in Application Example 1 before cycling;
[0032] Figure 3 SEM photos of the sulfur positive electrode of the lithium-sulfur battery using supramolecular conductive polymer TASP (a) and polyvinylidene fluoride (b) as binders before battery cycling and the battery using polyvinylidene fluoride (c) and supramolecular conductive polymer TASP (d) as binders after 50 cycles at a current density of 1C in Application Example 1 and Comparative Application Example 1;
[0033] Figure 4 CV curves of batteries using polyvinylidene fluoride (a) and supramolecular conductive polymer IASP (b) as binders in lithium-sulfur batteries in Application Example 2 and Comparative Application Example 1 between 1.6 and 2.8 V;
[0034] Figure 5 The rate performance test results (a) and the long cycle curve at 1C rate (b) of the battery using supramolecular conductive polymer (IASP) and polyvinylidene fluoride (PVDF) as binders in application example 2 and comparative application example 1 in lithium-sulfur batteries;
[0035] Figure 6 The rate performance test results (a) and the long cycle curve (b) at 2C rate of the battery using supramolecular conductive polymer (MASP) and polyvinylidene fluoride (PVDF) as binders in application example 3 and comparative application example 1 in lithium-sulfur batteries. DETAILED DESCRIPTION
[0036] The present invention provides a supramolecular conductive polymer having a structure shown in Formula I:
[0037]
[0039] In formula I, n: 24-32, m: 500-1000, x: 2084-2778;
[0040] R is an alkylene group, a substituted alkylene group, an aryl group, or a substituted aryl group.
[0041] In the present invention, the alkylene group preferably includes a straight chain alkylene group or a cycloalkylene group, the straight chain alkylene group preferably includes -CH2-CH2-CH2-CH2-CH2-CH2-CH2-, and the cycloalkylene group preferably includes the following structure:
[0042]
[0043] The substituted alkylene group preferably includes an ester-substituted alkylene group, and the ester-substituted alkylene group preferably includes the following structure:
[0044]
[0045] The aryl group preferably includes p-phenyl, m-phenyl or naphthyl, and the naphthyl group is preferably 1,5-naphthyl, with the following structural formula:
[0046]
[0047] The substituted aryl group preferably includes the following structure:
[0048]
[0049] In the present invention, the structural formula of the supramolecular conductive polymer is preferably as shown in Formula IV to VI:
[0050]
[0051]
[0052] With the values of m, n and x described in the present invention, the supramolecular conductive polymer has good mechanical properties and can be evenly spread when used as a binder.
[0053] The present invention also provides a method for preparing the supramolecular conductive polymer described in the above technical solution, comprising the following steps:
[0054] Mixing polyethylene glycol, isocyanate, malonic acid dihydrazide and an organic solvent to carry out a first polycondensation reaction to obtain a polyurethane solution;
[0055] The polyurethane solution and polyacrylic acid are mixed to carry out a second polycondensation reaction to obtain a supramolecular conductive polymer;
[0056] The structural formula of the isocyanate is shown in Formula II, and the structural formula of the polyacrylic acid is shown in Formula III.
[0057]
[0058] In formula III, y: 6250-8333.
[0059] In the present invention, unless otherwise specified, the materials and equipment used are commercially available products in the art.
[0060] The invention mixes polyethylene glycol, isocyanate, malonic acid dihydrazide and an organic solvent to carry out a first polycondensation reaction to obtain a polyurethane solution.
[0061] In the present invention, the structural formula of the polyethylene glycol is as follows:
[0062] Where n: 24~32.
[0063] In the present invention, the structural formula of the malonic acid dihydrazide is as follows:
[0064]
[0065] In the present invention, the isocyanate preferably includes toluene diisocyanate (TDI), diphenylmethane-4,4′-diisocyanate (MDI), xylylene diisocyanate (XDI), 1,6-hexamethylene diisocyanate (HDI), naphthalene-1,5-diisocyanate (NDI), methylcyclohexyl diisocyanate (HTDI), dicyclohexylmethane diisocyanate (HMDI), p-phenylene diisocyanate, 1,3-phenylene diisocyanate, toluene-2,6-diisocyanate or L-lysine diisocyanate.
[0066] In the present invention, the mass ratio of the polyethylene glycol, isocyanate and malonic acid dihydrazide is preferably 5:(3-4.5):(2-0.5), specifically 5:3:2.
[0067] In the present invention, the organic solvent preferably includes N,N-dimethylformamide and / or dimethyl sulfoxide.
[0068] In the present invention, based on 1 g of polyethylene glycol, the amount of the organic solvent used is preferably 20 to 50 mL.
[0069] In the present invention, the first polycondensation reaction is preferably carried out under an argon atmosphere, the temperature of the first polycondensation reaction is preferably 40 to 80°C, and the time is preferably 10 to 24 hours. The first polycondensation reaction is preferably carried out under stirring, and the present invention has no special requirements for the stirring speed. Taking N,N-dimethylformamide as an organic solvent, in the first polycondensation reaction process, polyethylene glycol, isocyanate and malonic acid dihydrazide undergo a polycondensation reaction to generate polyurethane, as shown in the following formula:
[0070]
[0071] After obtaining the polyurethane solution, the present invention mixes the polyurethane solution with polyacrylic acid to carry out a second polycondensation reaction to obtain a supramolecular conductive polymer.
[0072] In the present invention, the weight average molecular weight of the polyacrylic acid is preferably 45w to 60w.
[0073] In the present invention, the mass ratio of polyurethane to polyacrylic acid in the polyurethane solution is preferably 1:(1-2), specifically 1:1.
[0074] In the present invention, the second polycondensation reaction is preferably carried out under an argon atmosphere, the temperature of the second polycondensation reaction is preferably 30 to 60° C., and the time is preferably 24 to 48 hours. The second polycondensation reaction is preferably carried out under stirring, and the present invention has no special requirements for the stirring speed. During the second polycondensation reaction, polyurethane and polyacrylic acid are polycondensed to generate a supramolecular conductive polymer.
[0075] The present invention also provides the use of the supramolecular conductive polymer described in the above technical solution or the supramolecular conductive polymer obtained by the above preparation method in a positive electrode binder for a lithium-sulfur battery.
[0076] The present invention also provides a lithium-sulfur battery positive electrode, comprising a sulfur-carrying layer, wherein the sulfur-carrying layer comprises sulfur, a conductive agent and a binder, and the binder is the supramolecular conductive polymer described in the above technical solution or the supramolecular conductive polymer obtained by the above preparation method.
[0077] In the present invention, the conductive agent is preferably conductive carbon, and the conductive carbon preferably includes conductive carbon 350 and conductive carbon Super P.
[0078] In the present invention, the content of conductive carbon 350 in the sulfur-carrying layer is preferably 10-30wt%, more preferably 20-25wt%, specifically 21wt%; the content of sulfur is preferably 40-70wt%, more preferably 45-60wt%, specifically 49wt%; the content of conductive carbon Super P is preferably 1-30wt%, more preferably 5-25wt%, specifically 10wt%, 15wt% or 20wt%; the content of supramolecular conductive polymer is preferably 1-20wt%, more preferably 5-15wt%, specifically 10wt%.
[0079] In the present invention, the coating slurry for preparing the sulfur-carrying layer preferably includes an organic solvent, and the organic solvent preferably includes N-methyl-2-pyrrolidone (NMP) and / or N,N-dimethylformamide (DMF). The present invention preferably applies the coating slurry on the carbon-coated aluminum foil, and the present invention has no special requirements for the carbon-coated aluminum foil.
[0080] The present invention also provides a lithium-sulfur battery, comprising an electrolyte, a separator, a negative electrode and a positive electrode, wherein the positive electrode is the positive electrode of the lithium-sulfur battery described in the above technical solution.
[0081] In the present invention, the negative electrode is preferably metallic lithium.
[0082] In the present invention, the electrolyte preferably includes lithium bis(trifluoromethanesulfonyl)imide (LiTFSI) and lithium nitrate (LiNO 3 ), and the solvent of the electrolyte preferably includes 1,3-dioxolane (DOL) and / or ethylene glycol dimethyl ether (DME).
[0083] In order to further illustrate the present invention, the supramolecular conductive polymer and its preparation method and application, lithium-sulfur battery positive electrode and lithium-sulfur battery provided by the present invention are described in detail below in conjunction with the accompanying drawings and examples, but they should not be construed as limiting the scope of protection of the present invention.
[0084] In the embodiments or application examples of the present invention, LiTFSI is lithium bis(trifluoromethanesulfonyl)imide, and DOL / DME is 1,3-dioxolane / ethylene glycol dimethyl ether.
[0085] Example 1
[0086] Preparation of supramolecular conducting polymer (TASP):
[0087] S1, dissolving polyethylene glycol, toluene diisocyanate and malonic acid dihydrazide in dimethylformamide to obtain a mixed solution; wherein the mass ratio of polyethylene glycol, toluene diisocyanate and malonic acid dihydrazide is 5:3:2, and the volume of dimethylformamide is 20 mL based on 1 g of polyethylene glycol.
[0088] S2, placing the mixed solution obtained in step S1 in a heating stirrer for stirring, causing polycondensation reaction to obtain a polyurethane solution. The heating temperature is 40° C. and the stirring time is 10 hours.
[0089] S3, adding polyacrylic acid to the polyurethane solution, the mass ratio of polyacrylic acid to polyurethane is 1:1, heating and stirring, the heating temperature is 30°C, and the stirring time is 24 hours. The mixed solution obtained by the polycondensation reaction is dried in a vacuum oven at 80°C for 24 hours to obtain a supramolecular conductive polymer TASP.
[0090] Figure 1 This is the FT-IR spectrum of the supramolecular conductive polymer TASP prepared in Example 1. TASP is prepared by the polycondensation reaction of SPU (polyurethane) and PAA (polyacrylic acid), which can be fully verified by the results of FT-IR. SPU is at 1602 cm -1 The amide II band (NH bending vibration) at 1643 cm-1 was shifted to 1643 cm-1 containing TASP. -1 , indicating that the carboxylic acid moiety of PAA reacted successfully with the amide group of SPU.
[0091] Application Example 1
[0092] (1) Sulfur and conductive carbon (350) were mixed in a mass ratio of 7:3 and ground for 30 minutes. The color was uniform after grinding. Subsequently, the mixture was transferred into a 100 mL polytetrafluoroethylene kettle core and replaced with an argon atmosphere. The mixture was placed in an oven and heated at 155°C for 12 hours to allow sulfur to be composited with conductive carbon in a molten state. The mixture naturally cooled to room temperature to obtain a S / C composite.
[0093] (2) Prepare a DOL / DME (1:1, v:v) standard electrolyte containing 1 mol / L LiTFSI and 1 wt% lithium nitrate (LiNO3).
[0094] (3) The S / C composite, the conductive carbon SuperP and the supramolecular conductive polymer (TASP prepared in Example 1) were respectively prepared into sulfur-loaded positive electrodes at mass ratios of 6:3:1, 7:2:1 and 8:1:1, and then the above-mentioned sulfur-loaded positive electrodes, lithium metal negative electrodes and standard electrolytes were assembled into lithium-sulfur batteries, which were respectively denoted as TASP-631, TASP-721 and TASP-811, and the electrochemical performance was tested.
[0095] Figure 2The EIS spectrum of the sulfur positive electrode of the lithium-sulfur battery in Application Example 1 before cycling is shown in Table 1. The calculation results of the impedance and ionic conductivity of the lithium-sulfur battery in Application Example 1 are shown in Table 1. It can be seen that when the mass ratio of the S / C composite, the conductive carbon SuperP and the supramolecular conductive polymer (TASP) on the positive electrode is 7:2:1, the battery interface ohmic impedance of the positive electrode is the smallest, the ionic conductivity is the largest, and the reaction kinetics is the fastest.
[0096] Table 1 Calculation results of impedance and ion conductivity of lithium-sulfur battery in Application Example 1
[0097] name Thickness / cm Impedance / Ω <![CDATA[Ionic conductivity / S·cm -1 > TASP-631 0.0016 35 <![CDATA[2.33*10 -5 ]]> TASP-721 0.0018 21 <![CDATA[4.37*10 -5 ]]> TASP-811 0.0020 28 <![CDATA[3.64*10 -5 ]]>
[0098] Comparative application example 1
[0099] The difference from Application Example 1 is that the supramolecular conductive polymer in step (3) is replaced by polyvinylidene fluoride (PVDF), and the sulfur-loaded positive electrode is prepared according to the mass ratio of S / C composite, conductive carbon SuperP and polyvinylidene fluoride of 7:2:1. The remaining steps are the same as those in Application Example 1, which is recorded as S@C-PVDF.
[0100] Figure 3 SEM photographs of the sulfur positive electrode of the battery using supramolecular conductive polymer TASP (a) and polyvinylidene fluoride (b) as binders in the lithium-sulfur battery in Application Example 1 (TASP-721) and Comparative Application Example 1 before cycling, and of the battery using polyvinylidene fluoride (c) and supramolecular conductive polymer TASP (d) as binders after 50 cycles at a current density of 1C.
[0101] from Figure 3 It can be seen that after the battery cycle, the positive electrode of the lithium-sulfur battery using polyvinylidene fluoride (PVDF) as a binder showed serious cracks. In contrast, the positive electrode of the lithium-sulfur battery using a supramolecular conductive polymer (TASP) as a binder still maintained a relatively uniform surface after 50 cycles, with almost no signs of agglomeration or cracks. This is mainly due to the good self-healing ability of TASP, which can alleviate the irreversible damage caused by volume expansion of the sulfur positive electrode during battery cycling. TASP binder plays a key role in maintaining the structural integrity and stability of the sulfur positive electrode during the cycle process, thereby improving its electrochemical performance.
[0102] Example 2
[0103] Preparation of supramolecular conducting polymer (IASP):
[0104] The difference from Example 1 is that toluene diisocyanate in S1 is replaced by xylylene diisocyanate, and the remaining steps are the same as those in Example 1.
[0105] Application Example 2
[0106] The difference from Application Example 1 is that the supramolecular conductive polymer in step (3) is replaced by the IASP prepared in Example 2, and the S / C composite, conductive carbon SuperP and supramolecular conductive polymer (IASP) are prepared in a mass ratio of 7:2:1 to prepare a sulfur-loaded positive electrode, and the remaining steps are the same as those in Application Example 1, which is recorded as S@C-IASP.
[0107] Figure 4 CV curves of the battery using polyvinylidene fluoride (a) and supramolecular conductive polymer IASP (b) as binders in lithium-sulfur batteries in Application Example 2 and Comparative Application Example 1 between 1.6 and 2.8 V, with a scan rate of 0.1 mV s -1 .
[0108] from Figure 4 It can be seen that in the negative scan, the battery containing the S@C-IASP positive electrode has two reduction peaks at 2.35 and 2.04V, corresponding to the multi-step reduction process; in the positive scan, the lithium-sulfur battery with the S@C-IASP positive electrode has a set of overlapping oxidation peaks at 2.34 and 2.40V, corresponding to the oxidation process of Li2S or Li2S2. Compared with the CV curve of the battery containing the S@C-PVDF positive electrode, the battery containing the S@C-IASP positive electrode has a sharper redox peak and a smaller potential between the redox peaks, indicating that in the battery containing the S@C-IASP positive electrode, Li + It can move quickly at the interface between the electrode and the electrolyte and can diffuse quickly into the electrolyte, so its redox reaction process is more complete.
[0109] Figure 5 The rate performance test results (a) and the long cycle curve (b) at 1C rate of the battery using supramolecular conductive polymer (IASP) and polyvinylidene fluoride (PVDF) as binders in application example 2 and comparative application example 1 in lithium-sulfur batteries.
[0110] from Figure 5 It can be seen that the S@C-IASP cathode has excellent rate and cycle performance for lithium-sulfur batteries. The battery with S@C-PVDF cathode has a discharge specific capacity of 893.97 mAh / g when it is cycled from 5C rate to 0.2C rate. The battery using S@C-PVDF cathode is cycled 447 times at 1C with a capacity decay rate of 1.296%. The battery with S@C-IASP cathode has a discharge specific capacity of 994.91 mAh / g when it is cycled from 5C rate to 0.2C rate, which has excellent rate performance. The battery using S@C-IASP cathode is cycled 447 times at 1C with a capacity decay rate of 0.077%, which has excellent cycle performance.
[0111] Example 3
[0112] Preparation of supramolecular conducting polymer (MASP):
[0113] The difference from Example 1 is that the toluene diisocyanate in S1 is replaced by diphenylmethane-4,4′-diisocyanate.
[0114] Application Example 3
[0115] The difference from Application Example 1 is that the supramolecular conductive polymer in step (3) is replaced by MASP prepared in Example 3, and the S / C composite, conductive carbon SuperP and supramolecular conductive polymer (MASP) are prepared in a mass ratio of 7:2:1 to prepare the sulfur-loaded positive electrode, and the remaining steps are the same as those in Application Example 1, which is recorded as S@C-MASP.
[0116] Figure 6 The rate performance test results (a) and the long cycle curve (b) at 2C rate of the battery using supramolecular conductive polymer (MASP) and polyvinylidene fluoride (PVDF) as binders in application example 3 and comparative application example 1 in lithium-sulfur batteries.
[0117] from Figure 6 It can be seen that compared with the battery using PVDF as a binder, the lithium-sulfur battery with S@C-MASP cathode has excellent rate and cycle performance. The battery using PVDF as a binder maintains a capacity of 555.7 mAh g after 300 cycles. -1 The battery with S@C-PVDF cathode has a discharge capacity of 894.74 mAh / g when cycled from 5C to 0.2C. The battery using MASP as a binder has a capacity of 698.1 mAh·g after 300 cycles. -1 This shows that the battery with S@C-MASP cathode has good cycle performance. When the battery with S@C-MASP cathode is cycled from 5C rate to 0.2C rate, the discharge specific capacity reaches 981.65mAh / g, which has excellent rate performance.
[0118] The above electrochemical performance results show that the lithium-sulfur battery with supramolecular conductive polymer as the positive electrode binder has a higher discharge capacity and more stable cycle performance. The present invention overcomes the main challenges of lithium-sulfur batteries from the positive electrode aspect. By adding supramolecular conductive polymer as the positive electrode binder, the conductivity of the sulfur positive electrode can be improved, promoting the rapid transmission of lithium ions and electrons. At the same time, it can effectively adsorb polysulfides, which is very beneficial to the improvement of electrochemical performance.
[0119] Although the above-mentioned embodiments have made a detailed description of the present invention, they are only some embodiments of the present invention, rather than all embodiments. People can also obtain other embodiments based on the embodiments of the present invention without creative work, and these embodiments all fall within the scope of protection of the present invention.
Claims
1. A supramolecular conductive polymer, characterized in that: It has the structure shown in formula I: In formula I, n: 24-32, m: 500-1000, x: 2084-2778; R is an alkylene group, a substituted alkylene group, an aryl group, or a substituted aryl group.
2. The method for preparing the supramolecular conductive polymer according to claim 1, characterized in that: The following steps are involved: Mixing polyethylene glycol, isocyanate, malonic acid dihydrazide and an organic solvent to carry out a first polycondensation reaction to obtain a polyurethane solution; The polyurethane solution and polyacrylic acid are mixed to carry out a second polycondensation reaction to obtain a supramolecular conductive polymer; The structural formula of the isocyanate is shown in Formula II, and the structural formula of the polyacrylic acid is shown in Formula III. In formula III, y: 6250-8333.
3. The preparation method according to claim 2, characterized in that: The mass ratio of the polyethylene glycol, isocyanate and malonic acid dihydrazide is 5:(3-4.5):(2-0.5).
4. The preparation method according to claim 2 or 3, characterized in that: The temperature of the first polycondensation reaction is 40 to 80° C., and the time is 10 to 24 hours.
5. The preparation method according to claim 2, characterized in that: The mass ratio of polyurethane to polyacrylic acid in the polyurethane solution is 1:(1-2).
6. The preparation method according to claim 2 or 5, characterized in that: The temperature of the second polycondensation reaction is 30-60° C. and the time is 24-48 hours.
7. Use of the supramolecular conductive polymer according to claim 1 or the supramolecular conductive polymer obtained by the preparation method according to any one of claims 2 to 6 in a positive electrode binder for lithium-sulfur batteries.
8. A lithium-sulfur battery positive electrode, comprising a current-carrying layer, characterized in that: The sulfur-carrying layer comprises sulfur, a conductive agent and a binder, wherein the binder is the supramolecular conductive polymer according to claim 1 or the supramolecular conductive polymer obtained by the preparation method according to any one of claims 2 to 6.
9. The lithium-sulfur battery positive electrode according to claim 8, characterized in that: The content of the supramolecular conductive polymer in the sulfur-carrying layer is 1-20 wt %.
10. A lithium-sulfur battery comprising an electrolyte, a separator, a negative electrode and a positive electrode, characterized in that: The positive electrode is the lithium-sulfur battery positive electrode according to claim 8 or 9.
Citation Information
Cited By
Solid-state lithium-sulfur battery, manufacturing method thereof and electric equipment
CN120221782A